Experimental and computational approach on the corrosion inhibition properties of two newly pyrazole derivatives on carbon steel in acid medium - Nawal Setti; Asma Barrahi; Mohamed Maatallah; Yassine Kaddouri; Taibi Ben Hadda; Halima Outada; Abhinay Thakur; Rachid Touzani; Khalid Karrouchi; Hatem A. Abuelizz; Burak Dikici; Abdelkader Zarrouk; et al. (Scientific Reports)
Abstract In the current investigation, the efficiency inhibition of two newly synthesized bi-pyrazole derivatives, namely 2,3-bis[(bis((1 H-pyrazol-1-yl) methyl) amino)] pyridine (Tetra-Pz-Ortho) and 1,4-bis[(bis((1 H-pyrazol-1-yl) methyl) amino)] benzene (Tetra-Pz-Para) for corrosion of carbon steel (C&S) in 1 M HCl medium was evaluated. A Comparative study of inhibitor effect of Tetra-Pz-Ortho and Tetra-Pz-Para was conducted first using weight loss method and EIS (Electrochemical Impedance Spectroscopy) and PDP (Potentiodynamic Polarisation) techniques. Tetra-Pz-Ortho and Tetra-Pz-Para had a maximum inhibition efficacy of 97.2% and 96.2% respectively at optimum concentration 10−3mol/L and temperature 303 K, according to the data, suggesting that they are both effective inhibitors. The inhibition effectiveness of Tetra-Pz-Ortho and Tetra-Pz-Para increases significantly with higher concentration but decreases as temperature rises. The adsorption study demonstrated that the two molecules tested follow the Langmuir adsorption isotherm and chemically adsorbed on the metallic surface. The polarization methods showed that both compounds Tetra-Pz-Ortho and Tetra-Pz-Para were classified as mixed inhibitors. Based on the electrochemical impedance technique, the addition of the two inhibitors increased the charge transfer resistance and decreased the double layer capacity. In addition, the scanning electron microscopy (SEM) showed that the surface roughness of the C&S was considerably reduced in the presence of both Tetra-Pz-Ortho and Tetra-Pz-Para compared to its roughness without the inhibitors, indicated that the two inhibitors are effectively absorbed onto the carbon steel surface. These results were supported by elemental analysis of the metal/solution interface using X-ray photoelectron spectroscopy (XPS), for the two molecules tested. All studies demonstrated that the compound Tetra-Pz-Ortho is the most effective inhibitor. The DFT calculations and Monte Carlo/Molecular dynamic (MC/MD) simulations were treated and discussed for both compounds Tetra-Pz-Ortho and Tetra-Pz-Para in order to explain their interfacial approach and compared them to experimental results. The computational results of quantum chemistry were in agreement with those acquired by experimental methods.